Hubungan Pengetahuan Ibu Hamil Tentang Risiko Tinggi Dan Tanda Bahaya Pada Kehamilan, Persalinan, Nifas Dengan Sikap Dan Perilaku Ibu Dalam Perawatan Kehamilan - Rianti, Agus; Mikawati; Asriyanti; Muaningsih; Pratiwi, Rizky (PT. Pubsains Nur Cendekia, 2024)
High risk pregnancy is a dangerous pregnancy. Can cause major complications in the mother and fetus in the womb, compared to normal pregnancy, childbirth, postpartum. Aim research is to determine the relationship between pregnant women's knowledge about high risks and danger signs of pregnancy, childbirth, postpartum with attitudes and behavior in pregnancy care. Research method use descriptive analytics with a cross-sectional design. Sample 95 with accidental sampling technique. Chi-square test data analysis. Results are Of the 95, 11(11.6%) had good knowledge, 84(88.4%) had poor knowledge, 15(15.8%) had positive attitudes, 80(84.2%) had negative attitudes, 14(14.2%) positive attitudes. .7%), negative behavior 81(85.3%). The results of the test using chi-square showed that there was a relationship between knowledge and attitude, with a p-value of 0.000 <0.05 and between knowledge and behavior, a p-value of 0.000 <0.05 was obtained. There is a relationship between knowledge about high risks and danger signs of pregnancy, childbirth, postpartum with attitudes and behavior in pregnancy care.